Evolution and development of potent monobactam sulfonate candidate IMBZ18g as a dual inhibitor against MDR Gram-negative bacteria producing ESBLs - Li, Zhiwen; Guo, Zhihao; Lu, Xi; Ma, Xican; Wang, Xiukun; Zhang, Rui; Hu, Xinxin; Wang, Yanxiang; Pang, Jing; Fan, Tianyun; Liu, Yonghua; Tang, Sheng; et al. (Acta pharmaceutica Sinica. B, 2023)
A series of new monobactam sulfonates is continuously synthesized and evaluated for their antimicrobial efficacies against Gram-negative bacteria. Compound 33a (IMBZ18G) is highly effective in vitro and in vivo against clinically intractable multi-drug-resistant (MDR) Gram-negative strains, with a highly druglike nature. The checkerboard assay reveals its significant synergistic effect with β-lactamase inhibitor avibactam, and the MIC values against MDR enterobacteria were reduced up to 4–512 folds. X-ray co-crystal and chemoproteomic assays indicate that the anti-MDR bacteria effect of 33a results from the dual inhibition of the common PBP3 and some class A and C β-lactamases. Accordingly, preclinical studies of 33a alone and 33a‒avibactam combination as potential innovative candidates are actively going on, in the treatment of β-lactamase-producing MDR Gram-negative bacterial infections. IMBZ18G is highly effective against MDR Gram-negative bacteria, with the dual inhibition on PBP3 and class A and C β-lactamases. IMBZ18G-avibactam combination further broadens the antibacterial application of IMBZ18G. [Display omitted]